Lemon peel based activated carbon and their composite with metal nanoparticles as efficient catalysts for the reduction of organic dyes and hydrogen production - Albandary S. Almaghrabi; Esraa M. Bakhsh; Kalsoom Akhtar; Maram A. Alghamdi; Sher Bahadar Khan (Results in Chemistry)
Water treatment and hydrogen production are essential areas of sustainability. In this research, silver nanoparticles (AgNPs) and copper nanoparticles (CuNPs) were grown on lemon peels (LPAC) based activated carbon, which act as support for AgNPs and CuNPs. LPAC, AgNPs@LPAC and CuNPs@LPAC were utilized for the enhanced selective reduction of Alizarin Yellow R (AYR) dye and hydrogen production by the hydrolysis of NaBH4. Effective catalytic reduction was successfully achieved with AgNPs@LPAC while LPAC was more effective in hydrogen generation. Under optimized conditions, AgNPs@LPAC showed complete reduction of AYR in 5 min with fast AYR reduction kinetics (k = 0.4934 min−1). Among the developed catalysts, LPAC demonstrated fast H₂ generation with a high H₂ generation rate (HGR = 382.400 mL (g. min)−1 under optimized conditions. Moreover, the Ea energy of 54.91 kJ/mol for hydrogen production by the LPAC catalyst was calculated at various temperatures. The deactivation of both AgNPs@LPAC and LPAC was negligible during recycling, highlighting their potential for practical applications in environmental remediation and hydrogen production.